Metode Istinbat Imam Malik - Husnul Khatimah (Program Pascasarjana Universitas Ibrahimy, 2017)
The proverb that probably almost every Indonesian knows it, “unknown unloved.” That is proverb perhaps described what will be explained in this simple article. This article seeks to know one of the great teachers whom had been meritorious in the development of Islam. He is Imam Malik bin Anas, the Islamic scholar of hadith and fiqh specialist. He is the central figure of the Maliki Madh-hab, one of the Islamic major streams in the world. This article will be explained about Imam Malik argument which has relation with intinbath method for getting Islamic law, as we have known he is one of the mujtahid mutlaq. Istinbat method was done by Imam Malik with reviewed Al-Qur’an, Al Sunnah, Ijma’ Ahl al-Madinah, Fatwa Sahabat, Khabar Ahad dan Qiyas, Al-Istihsan, Al-Maslahah al- Mursalah, Sadd al-Zhari'ah, Istishab, Syar'u Man Qoblana. Books that wich used for references in Maliki Madh-hab such as Al-Mudawwanah Al-Kubra, Bidayatul Mujtahid wa Nihayatul Muqtashid (by Ibnu Rusyd), Matan Ar-Risalah fi Al-Fiqh Al-Maliki (by Abu Muhammad Abdillah bin Zaid), Ashl Al-Madarik Syarh Irsyad Al-Masalik fi Fiqh Al-Imam Malik (by Syaikh Shihabuddin Al-Baghdadi), dan Bulghah As-Salik li Aqrab Al-Masalik (by Syaikh Ahmad As-Shawi).